Scat Singing: A Timbral and Phonemic Analysis - Bauer, William R. (Current Musicology, 2001)
In this article William Bauer analyzes scat and timbre within the context of Jazz and their effects on music over time. He concludes that for many vocalists timbre is much more than a vehicle for adding coloristic touches to a melodic line. But while singers’ distinctive use of timbre sets their work apart from that of instrumentalists, the crossover of ideas between instrumentalists and vocalists indicates that the timbral analysis of scat vocals may offer insights that are applicable to instrumental music. Regardless of this potential application, however, it is evident that by closely examining how singers exercise mastery over timbre as well as other musical raw materials we can increase our understanding of singers’ accomplishments and deepen our appreciation of their contribution to jazz.